Penggunaan Bahasa Gaul Dikalangan Remaja Dalam Menggunakan Twitter - Salma Sabila Azka; Samuel Tulus Hati Karo-Karo (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
In today's digital era, we often hear or see the use of slang words, both among teenagers and adults. We often find slang words on social media users, one of which is Twitter. The rapid development of communication technology in this digital era, so that social media is very easy to access, in general social media such as twitter most of its users are teenagers. In the end, it has a major influence on how to interact in social life both in cyberspace and the real world. Some experts state that the characteristics of the generation in the current era are different from the previous generation, one of the reasons is because the current generation was born and grew up in a modern environment and surrounded by digital technology. This study aims to identify the various forms of slang found in captions and comment columns on social media twitter. The data in this study is in the form of slang words obtained by applying observation methods with screenshot and record techniques. The data sources used were @collegemenfess Twitter social media accounts and @kdrama_menfess. The results in this study are various forms of slang words in the form of (1) mager, (2) bucin, (3) baper, (4) gabut, (5) bm, (6) gaje, (7) gercep, (8) mode. The analysis showed mixed results, but most of the participants stated that they got slang words to interact with in social circles and obtained those slang words from memes and other social media.